A review of the genus Eotmethis (Orthoptera, Acridoidea, Pamphagidae) with two new species and key to known species of the genus from China - Li, Xin-Jiang; Shi, Jian-Ping; Dang, Yan (Zootaxa, 2016)
Two new species of the genus Eotmethis Bey-Bienko, 1948, namely Eotmethis inditibialis sp. nov. and Eotmethis shizuishanensis sp. nov. from the Ningxia Hui Autonomous Region are described in this paper. The new species Eotmethis inditibialis sp. nov. differs from all known species of the genus by inner side of hind tibia purple in the middle. The new species Eotmethis shizuishanensis sp. nov. is similar to Eotmethis xiai Ye, Shi & Zhi, 2015, differs from latter by tegmina of male shorter, reaching to 4th abdominal tergite, R vein without branch, M vein with one branch, Cu vein without branch and lower knee-lobe of hind femur yellow on inner side. The type specimens are deposited in College of Life Sciences, Hebei University, Baoding, China. Key to known species of the genus Eotmethis Bey-Bienko, 1948 is given.